PRR5, 7 and 9 positively modulate TOR signaling-mediated root cell proliferation by repressing TANDEM ZINC FINGER 1 in Arabidopsis - Li, Bin (Nucleic Acids Res, 2019)
Circadian clock coordinates numerous plant growth and developmental processes including cell elongation in the hypocotyl, whether or not it modulates cell proliferation is largely unknown. Here we have found that Pseudo Response Regulators (PRRs), essential components of circadian core oscillators, affect root meristem cell proliferation mediated by Target Of Rapamycin (TOR) signaling. The null mutants of PRRs display much reduced sensitivities to sugar-activated TOR signaling. We have subsequently identified Tandem Zinc Finger 1, encoding a processing body localized RNA-binding protein, as a direct target repressed by PRRs in mediating TOR signaling. Multiple lines of biochemical and genetic evidence have demonstrated that TZF1 acts downstream of PRRs to attenuate TOR signaling. Furthermore, TZF1 could directly bind TOR mRNA via its tandem zinc finger motif to affect TOR mRNA stability. Our findings support a notion that PRR-TZF1-TOR molecular axis modulates root meristem cell proliferation by integrating both transcriptional and post-transcriptional regulatory mechanisms.